2014
DOI: 10.7860/jcdr/2014/7990.4364
|View full text |Cite
|
Sign up to set email alerts
|

“Evaluation of Friction in Orthodontics Using Various Brackets and Archwire Combinations-An in Vitro Study”

Abstract: AIM:The aim of this study was to compare frictional resistance which was produced between conventional brackets (0.022 slot Otho-Organiser) and self ligating brackets (active Forestadent and passive Damon III) by using various arch wire combinations (0.016 Niti, 0.018 Niti, 0.017 x 0.025 SS and 0.019 x 0.025 SS). Materials and Methods:An experimental model which consisted of 5 aligned stainless steel 0.022-in brackets was used to assess frictional forces which were produced by SLBs (self ligating brackets) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Based on this study, the authors could affirm that the metal brackets had a frictional force that was equal to that of self-ligating brackets, in disagreement with some authors who also compared the frictional force between self-ligating and metal brackets, an found results indicating that the force calculated on metal brackets was significantly higher than that on self-ligating brackets 12,16,17 . On the other hand, the authors 18 compared the frictional force in sliding by using stainless steel self-ligating brackets and conventional stainless steel brackets with steel 0.019 x 0.025 inches archwires, and concluded that the self-ligating brackets presented higher frictional force values when compared with the conventional type.…”
Section: Discussioncontrasting
confidence: 73%
“…Based on this study, the authors could affirm that the metal brackets had a frictional force that was equal to that of self-ligating brackets, in disagreement with some authors who also compared the frictional force between self-ligating and metal brackets, an found results indicating that the force calculated on metal brackets was significantly higher than that on self-ligating brackets 12,16,17 . On the other hand, the authors 18 compared the frictional force in sliding by using stainless steel self-ligating brackets and conventional stainless steel brackets with steel 0.019 x 0.025 inches archwires, and concluded that the self-ligating brackets presented higher frictional force values when compared with the conventional type.…”
Section: Discussioncontrasting
confidence: 73%
“…For this purpose, a periodontal ligament/non-linear bone system was used (23); this permits a closer approach to clinical reality. First, it was found that, for both bracket systems, the distribution of stresses showed a higher concentration on neck and root, especially on anterior teeth, which can be explained by the fact that this is the area of closer proximity to the of application of the stress; the middle area of periodontal ligament shows lower rigidity than the apical (2). Additionally, and bearing in mind the distribution of loads on the root surface during the uncontrolled inclination, where center of resistance and rotation coincide during the initial alignment stages, the uncontrolled inclination results in a distribution of higher load on the neck, where the expression of rotational tendency of this type of movement starts (24).…”
Section: Discussionmentioning
confidence: 99%
“…Frictional resistance is the force that delays or impedes movement between two objects that are in contact (1). In orthodontic biomechanics, the capacity of the archwire to slide through brackets and tubes is essential to achieve proper alignment and leveling since dental movement is only possible when the stress applied exceeds the friction caused during the bracket/archwire interface (2). High levels of frictional force between the slot and the archwire may cause binding of these two components, which would result in a shallow (if any) dental movement.…”
Section: Introductionmentioning
confidence: 99%
“…According to him, SLBs had lesser frictional resistance than steel or elastomeric-tied conventional brackets (13). Other studies also found the same conclusion (8,(14)(15)(16)(17)(18). In an in-vitro study by Vinay K which assessed friction in different combinations of wire, bracket and ligation method, it was concluded that self-ligating brackets offered least friction followed by conventional stainless steel brackets, ceramic with metal insert bracket and ceramic brackets (19).…”
Section: Resistance To Slidingmentioning
confidence: 93%